Os bárbaros estão chegando': o processo de democratização do governo Richa no Paraná - Kuiava, José (1993)
The present academic research analyses the political conjuncture of the democratic transitional process that happened in Brazil and in the State of 'Parana' in the end of the nineteen seventies and in the beginning of the nineteen eighties. In the first chapter I examine the theoretical and methodological elements which constitute the analytical categories I use to study the concrete Brazilian situation, in a broad sense, and, in a more particular one~ the conjuncture of the nineteen eighty-two's election and Jose Richa's Goverment in Parana. It was necessary to e>:amine the 'broad' conception of State, the concepts of structure and superstructure of the historic block, as well as the concepts of liberal and popular democracies, according to dialectic and historical materialistic literature, other classic and modern authors. In the second chapter, I examine the transitional democratic project from President Geisel to President Figueiredo: a military and Brazilian elite's plan to save themselves on power by making a political transition by the top of society. The project aimed, in a doubtful electoral process, to legitimate the political regime and economic model through passing military government to civil government. In the State of Parana, the main aim of this research, I analyse the liberal project of Richa's PMDB's government, from the organization of the party, the elaboration of the government's lines, the electoral campaign and high intellectual's participation in it, PMDB's alliances with popular social groups up to government’s composition and 'righting' process. 'THE BARBARIAN ARE ARRIVING', main title of this thesis, was the way that Curitiban aristocracy (elite) referred to Jose Richa when he was elected to the government of the State of Parana, because he was born in an interior city and so he did not belong to the 'civilized' and 'cosmopolitan' Curitiban society. In the third chapter I analyse the democratization of public schools expressed by their directors' elections through teachers', other school employees', students' and their parents' votes. I assert that democracy goes beyond a government's decree to establish the electoral system. I still assert that in Richa's government, discourse becomes another thing when it comes into practice, particulary in the educational system. The basic question of this research is to work the idea that education is an area of social classes', disputes and confronts to get hegemonic power. The upper social class strugles to rema in in power, while the lower social classes sometimes become alied to the upper class and help it, sometimes simply consent to it, but very seldom revolt against its domination.